Analysis of the Effectiveness of Using Audio Visual Media in Science Learning in Elementary Schools - Mar'atus Sholihah; Rohmani (Universitas Pendidikan Ganesha, 2024)
Audiovisual learning tools are utilized in the educational process to deliver subject content by integrating sound and visual elements. This study aims to evaluate the effectiveness of audiovisual media in teaching Natural Sciences (IPA) at the elementary school level. The research method employed is a Systematic Literature Review (SLR), utilizing the Google Scholar database. The literature review was conducted in three stages. Initially, the keyword